Amikor (látszólag) semmi sem történik – A fontolgatás mint a változás feltétele - SIBA, Balázs (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2022)
When (Seemingly) Nothing Happens – Reflection as a Precondition for Change. This is the first of an eight-part series of essays primarily for young adults and those helping them to grow up (parents, teachers, mentors). The entire series deals with the “heroic journey” of growing up, following the monomyth transformation scenario described by Joseph Campbell. This archetypal journey begins with the prelude to change, with the discovery of worlds outside “my world”. Contemplation is part of all our lives, even if we do not foster it so consciously. Whether it takes the form of talking to others, an inner monologue, or a prayer to God, contemplation is important because together with pondering it can be a precursor to life-changing events. Change begins with a sense of lack, of being unsettled, but losing focus is part of the search for a way out. It is usually not easy to remain in a state of cluelessness, of being at a loss, but being out of focus is a chance to deepen our connection to ourselves and to move inner energies that can intuitively help us to find the solution to our questions of life.